Neonatal near miss in the intensive care unit - Maria Rita Guimarães Maia; Rosângela Aparecida Pimenta Ferrari; Alexandrina Aparecida Maciel Cardelli; Ieda Harumi Higarashi; Maria Dalva de Barros Carvalho; Sandra Marisa Pelloso (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze near miss cases among newborns hospitalized in the Intensive Care Unit. Methods: An observational, cross-sectional, retrospective study using the STROBE guideline. Data were collected from 1,101 records of live births (newborns). Statistical analysis used the Epi-Info program 3.3.2 and Chi-square and Fisher's exact tests. Results: A total of 162 newborns were hospitalized, of which 63 had at least one criterion of near miss. The variables that remained associated with neonatal near miss were weight <1.750 g, gestational age <33 weeks and Apgar at 5 minutes <7, pragmatic criteria to identify cases of neonatal near miss morbidity. Conclusion: Prematurity and low birth weight were the factors that contributed most to the near miss outcome among newborns hospitalized in intensive care, a rate two and a half times higher than the number of deaths, according to scientific evidence.